Adhesion performance of a universal adhesive in the root canal: Effect of etch-and-rinse vs. self-etch mode - Shafiei, Fereshteh (PLoS One, 2018)
PURPOSE: Universal adhesives are new systems that can be used in etch-and-rinse (ER) and self-etch (SE) modes. This in vitro study evaluated the bonding performance of a universal adhesive in ER mode and SE mode with two irrigants for luting fiber posts in the root canal. MATERIALS AND METHODS: After separation of the roots from the crowns of 56 maxillary central incisors and endodontic treatment, 10-mm post space was prepared. The roots were divided into seven groups according to irrigant/adhesive protocol used for cementation of posts: 1) sodium hypochlorite (NaOCl) irrigant + acid etching + One-Step Plus, 2) NaOCl + Clearfil SE Bond (CSE) and 3) EDTA + CSE as controls; 4) NaOCl + All-Bond Universal (AB) in ER mode, 5) NaOCl + AB in SE mode, 6) EDTA + AB in SE mode, 7) distilled water + AB in SE mode. Posts were luted using Duo-link. The bonded roots were sectioned into microslices. After push-out bond strength (PBS) testing, data in MPa were analyzed with two-way ANOVA and Tukey test (α = 0.05). RESULTS: PBS was significantly affected by irrigation/adhesive protocol and root region (P<0.05), with no significant interaction of these factors. PBS of ABU in ER mode with NaOCl and in SE mode with NaOCl or EDTA was comparable to that in the respective controls. The highest and lowest PBSs were recorded for ABU in the SE mode with EDTA (15.38 ± 4) and NaOCl (10.17 ± 3.5), respectively. PBS of AB in ER and SE modes was similar when distilled water was used in the SE mode. CONCLUSION: Adhesive performance of AB in the ER mode was comparable to or different from the SE mode, depending on the irrigant used to prepare post space in SE approach. AB could behave as a reliable bonding for post cementation.